디지털 유방촬영장치에서 다엽 조리개 적용으로 인한 화질과 선량의 변화 - 권순무; Soon Mu Kwon; 김부순; Boo Soon Kim; 박형준; Hyung Jun Park; 강영한; Yeong Han Kang (한국방사선학회 논문지, 2015)
X선 조사야(X-ray beam field)는 X선관 앞에 부착된 선속제한기구(beam limiting device)인 조리개(collimator)에 의해 조절된다. 조리개는 1차 X선을 조절하여 환자의 피폭선량을 감소시키고 산란선량을 감소시켜 영상의 화질을 향상시키는 중요한 기능을 한다. 그러나 유방촬영장치의 조리개에 대해서 따로 규정되어 있지 않으며 상업화된 장치에서는 조사야가 사각형으로 조절되는 조리개를 사용하고 있다. 최근 디지털 유방촬영장치의 보급이 확대되고 있으나 film/screen방식에서부터 적용되던 사각형으로 조사야가 조절되는 조리개가 사용되고 있다. 따라서 본 연구에서는 디지털 유방촬영에서 조사야 조절 사용에 대한 실태조사 후 유방의 크기와 모양에 따라 조사야를 조절할 수 있는 다엽조리개를 제작 후 적용했을 때 영상의 화질변화와 평균유선선량, 면적선량 값의 변화를 알아보았다. 사각형으로 조사야가 조절되는 조리개와 비교하여 다엽 조리개를 적용한 영상에서 통계적으로 유의한 차이가 없었으며 DAP값 또한 50.72% 감소되었다. 따라서 디지털 유방촬영장치에서 조사야를 최적화하기 위한 자동조사야조절장치 개발이 환자 피폭선량 감소에 도움이 될 것으로 판단된다. Collimator has important functions with control primary X-ray that decrease radiation exposure dose for patients and reduce scatter ray and make better quality of image. But there are no regulations for X-ray mammography device of collimator, so widely used device adopt rectangularly controlled collimator. Though digital X-ray mammography device expand supply recently, rectangularly controlled collimator of film/screen mode still used. After searching for real condition of beam field with digital mammography, we made a multi-leaf collimator which is able to adjust the beam field in accordance with size and shape of breast, and we measuring up the transitions of image quality, average glandular dose(AGD) and, Dose area product(DAP). There are no significant differences between rectangularly controlled collimator and multi-leaf collimator, and DAP value decreased by 50.72%. As conclusion, there needs to expand the use of multi-leaf collimator for optimum adoption of beam field in digital mammography, and also need to develop an automatic regulation of beam field for reduce of exposure dose to patients.